Three-dimensional MHD modeling of vertical kink oscillations in an active region plasma curtain - Ofman L.; Parisi M.; Srivastava A.K. (My University, 2025)
Context. Observations on 2011 August 9 of an X 6.9-class flare in active region (AR) 11263 by the Atmospheric Imaging Assembly (AIA) on board the Solar Dynamics Observatory (SDO), were followed by a rare detection of vertical kink oscillations in a large-scale coronal active region plasma curtain in extreme UV coronal lines with periods in the range 8.8-14.9 min. Aims. Our aim is to study the generation and propagation of the magnetohydrodynamic (MHD) oscillations in the plasma curtain taking the realistic 3D magnetic and the density structure of the curtain into account. We also aim to test and improve coronal seismology for a more accurate determination of the magnetic field than with the standard method. Methods. We use the observed morphological and dynamical conditions, as well as plasma properties of the coronal curtain, to initialize a 3D MHD model of the observed vertical and transverse oscillations. To accomplish this, we implemented the impulsively excited velocity pulse mimicking the flare-generated nonlinear fast magnetosonic propagating disturbance interacting obliquely with the curtain. The model is simplified by utilizing an initial dipole magnetic field, isothermal energy equation, and gravitationally stratified density guided by observational parameters. Results. Using the 3D MHD model, we are able to reproduce the details of the vertical oscillations and study the process of their excitation by a nonlinear fast magnetosonic pulse, propagation, and damping, finding agreement with the observations. Conclusions. We estimate the accuracy of simplified slab-based coronal seismology by comparing the determined magnetic field strength to actual values from the 3D MHD modeling results, and demonstrate the importance of taking more realistic magnetic geometry and density for improving coronal seismology into account. © ESO, 2015.